The Impact of COVID‐19 on CO2 Emissions in the Los Angeles and Washington DC/Baltimore Metropolitan Areas. Issue 11 (7th June 2021) - Yadav, Vineet; Ghosh, Subhomoy; Mueller, Kimberly; Karion, Anna; Roest, Geoffrey; Gourdji, Sharon M.; Lopez‐Coto, Israel; Gurney, Kevin R.; Parazoo, Nicholas; Verhulst, Kristal R.; Kim, Jooil; Prinzivalli, Steve; et al.
Abstract: Responses to COVID‐19 have resulted in unintended reductions of city‐scale carbon dioxide (CO2 ) emissions. Here, we detect and estimate decreases in CO2 emissions in Los Angeles and Washington DC/Baltimore during March and April 2020. We present three lines of evidence using methods that have increasing model dependency, including an inverse model to estimate relative emissions changes in 2020 compared to 2018 and 2019. The March decrease (25%) in Washington DC/Baltimore is largely supported by a drop in natural gas consumption associated with a warm spring whereas the decrease in April (33%) correlates with changes in gasoline fuel sales. In contrast, only a fraction of the March (17%) and April (34%) reduction in Los Angeles is explained by traffic declines. Methods and measurements used herein highlight the advantages of atmospheric CO2 observations for providing timely insights into rapidly changing emissions patterns that can empower cities to course‐correct CO2 reduction activities efficiently. Plain Language Summary: In this study, we use atmospheric CO2 observations from urban measurement networks in Los Angeles and Washington DC/Baltimore to detect the onset of the pandemic response. We show that April 2020 emissions were ∼30% lower than in previous years in both metropolitan areas. Decreases in vehicular traffic do not completely explain the observed emissions reductions, demonstrating the complex interplay of human activities and atmospheric dynamics that drive CO2 emissions at the urban scale. Key Points: Atmospheric CO2 observations can be used to detect the onset of the COVID‐19 response in Los Angeles and Washington DC/Baltimore Relative reductions in April 2020 associated with COVID‐19 are ∼30% when compared to emissions in 2018 and 2019 Decreases in vehicular traffic do not completely explain observed emissions reductions in both Los Angeles and Washington DC/Baltimore